Analisis Puisi “Tapi” Karya Sutardji Calzoum Bachri Dengan Menggunakan Pendekatan Struktural (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
Basically, literary works are works that are written in beautiful and orderly language. According to Taum (1997) literature is a form of creation or fiction that is imaginative and uses beautiful language and its presence can be used for other things. One example of a form of literary work is poetry. Poetry is a literary work of high value. Poetry is a literary work that is created as an expression of the wishes, circumstances, and feelings of the author as outlined in poetry (Putu Sudarma 2019). This study discusses the study of a literary work of poetry entitled "But" by Sutardji Calzoum. Bachri. The purpose of this research is to analyze the structure of the poem "But" by Sutardji Calzoum Bachri. Structural Analysis is a tool for studying poetry based on the structure that builds poetry. The method used in this research is descriptive qualitative method. The technique in presenting data is based on objective reality by examining poetry. In this case, the building blocks of poetry are the physical structure and the inner structure. The physical structure consists of the form of poetry, diction, concrete words, figurative language and imagery. Meanwhile, the inner structure that is analyzed in poetry is in the form of theme, tone, atmosphere and message. Both of these structures are the forming elements of the creation of poetry.